2016
DOI: 10.1007/s11657-015-0256-x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in patients admitted to the general ward with breast, lung, and colorectal cancer in Buenos Aires, Argentina

Abstract: The study found a high prevalence of vitamin D deficiency in hospitalized cancer patients under active treatment. Many authors have recommended dosing vitamin D levels in this population; normalizing serum levels is difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…In 2014, a meta-analysis by Chowdhury et al [39] observed a 16% increase in mortality for every decline of 10 ng/mL in the serum vitD levels. Moreover, among cancer patients, a high prevalence (about 70%) of vitD deficiency has been reported [40] , lower in outpatients (48%) than inpatients (up to 97.5%) [41][42] . Accordingly, in our study, 68% of NEN patients had vitD deficiency, but in contrast to the studies that demonstrated an inverse correlation between vitD levels and colorectal carcinoma staging [43][44] , in this study no significant correlation with vitD levels and the staging or grading of the disease was found.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, a meta-analysis by Chowdhury et al [39] observed a 16% increase in mortality for every decline of 10 ng/mL in the serum vitD levels. Moreover, among cancer patients, a high prevalence (about 70%) of vitD deficiency has been reported [40] , lower in outpatients (48%) than inpatients (up to 97.5%) [41][42] . Accordingly, in our study, 68% of NEN patients had vitD deficiency, but in contrast to the studies that demonstrated an inverse correlation between vitD levels and colorectal carcinoma staging [43][44] , in this study no significant correlation with vitD levels and the staging or grading of the disease was found.…”
Section: Discussionmentioning
confidence: 99%
“…Another common theme found in the literature is the association of VDD and cancer development, namely colon, prostate, and breast cancer (Iruzubieta et al, 2014;Stein et al, 2009;Stokes et al, 2014;Villar et al, 2013). VDD is prevalent among cancer patients with one study showing 74% of breast cancer patients to be low in VD and VDS conferring a 15% decrease in mortality among lung cancer patients (Aguirre et al, 2016). Relevant to liver disease is that hepatocellular and intrahepatic cholangiocarcinoma often develop in patients with cirrhosis and is inversely related to levels of VD (Stokes et al, 2013).…”
Section: Sustained Virologic Responsementioning
confidence: 99%
“…Individuals at risk for bone loss are recommended to consume 1200 to 1500 mg of calcium and 400 to 600 IU of vitamin D per day; however, there are no established guidelines for calcium and vitamin D in patients with cancer . Studies have shown that 70% to 97.5% of patients with cancer are vitamin D deficient . Calcium levels in patients with cancer vary.…”
Section: Exercise and Nutritional Interventionsmentioning
confidence: 99%